THE URGENCY OF DEVELOPING SOCIAL LEARNING BASED ON LOCAL WISDOM - Made Ayu Anggreni; Wahyuni H.Mailili, Siti Hadija Alaydrus, Windra; Risnawati Yusuf (Adisam Publisher, 2024)
This literature review aims to describe the urgency of developing social studies learning based on local wisdom. Teachers can develop contextual learning by conducting learning based on local wisdom around students. Teachers can integrate social studies material with local wisdom so that students are interested and can understand the material well so that student learning outcomes are maximized. The use of local wisdom in social studies learning is a culture-based learning dimension that utilizes various forms of culture that are rich in social and cultural values. The values contained in local wisdom can be used as one of the social studies learning resources, with the hope that it can provide concrete learning experiences to students and learning will be meaningful. The values in local wisdom can be implemented in social studies learning, whether it is affective learning, namely related to character values, or cognitive learning, namely related to science. Through social studies learning that is oriented towards local wisdom, we can become a shield against the flow of globalization.